Effect of Water Soluble Substances of Licorice (Glycyrrhiza glabra L.) on the Grovth of Algae and some vater properties of the Refinary unit of Babylon University Campus (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
see pdf please